Conceptualizing distributive justice in education: a complexity theory perspective - Gilead, Tal (Journal of philosophy of education, 2023)
Over the last two decades, complexity theory, which is designed to deal with systems of multiple interdependent variables, has been increasingly applied to analyse and shed light on various aspects of education. So far, however, complexity theory has rarely been used, if at all, to examine questions related to educational justice. This article offers a theoretical examination of some possible links between complexity theory and distributive justice in education. It asks how accepting the premise that education is a complex dynamic system should shape the way distributive justice in education is conceptualized and approached. It is argued that complexity theory challenges many assumptions on which the dominant approach for dealing with distributive justice in education rests. The article focuses on three subjects that stem from complexity theory but have implications for dealing with distributive justice in education: system diversity, reductionism, and change. Each of these subjects is examined separately, and some possible contributions of complexity theory to illuminating these subjects in relation to distributive justice in education are discussed. The article ends with a brief illustration of where a complexity-based approach to educational justice leads that focuses on school choice and contrasts it with Brighouse's views on this issue.